Faded memories: The role of design in enhancing the quality of life of persons living with dementia - I. T. A. O Frimpong; D. Y. A Duah; A. B Marful; I. E Kwofie; J. K Offei-Nketiah (Cogent Gerontology)
In Sub-Saharan African, specifically Ghana, the prevalence of dementia, has made the lack of care options available for the aged, a pressing issue. Combined with the slow deterioration of the traditional family system in Ghana and the rapid ageing of the population, the situation seems dire. Experts related to dementia are also severely lacking with care predominantly provided through mental health services. The research supports the provision of a better quality of life for persons living with dementia through dementia-friendly architectural interventions. Data was obtained through the review of 277 publications focused on dementia in Ghana, 2 case studies, as well as the thematic analysis of 15 semi-structured interviews of purposively sampled respondents. The study identified that persons living with dementia in Ghana face challenges with care, with design modifications made based on the needs of the individuals, but without specific guidance. Thus, a design framework is necessary to maximise the effects of design on the quality of life of persons living with dementia. Hitherto, no previous study in Ghana has focused on the living space as an alternative care option for dementia. The Ghanaian context allows for replication of results in other developing nations due to similar socio-economic characteristics.